PENGARUH OPTIMISME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA SMA - Lenny Kurniati; Asef Umar Fakhruddin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Optimists are people who expect the good thing in the future. This paper focusing in particular on how optimism may lead a person, especially a student to cope and solve a  problem. The primary pupose of this paper is to review the beneficial effect of optimism, on students problem solving abilities. This study was conducted on 164 high school students using an optimism questionnaire instrument and a test of mathematical problem solving abilities. The result show that optimism and students' mathematical problem solving abilities have a positive and significant relationship, its indicated by the r product moment score of 0.79. In addition correlation were obtained optimism influences students' mathematical problem solving abilities by 63%. Further research is needed to improve students' ability to solve mathematical problems through optimism.Keywords: optimism, problem solving ability, mathematics, education